German works councils - a model for South African workplace forums? - Rohr, Selina (Department of Commercial Law, 2018)
The aim of the introduction of workplace forums in South Africa in 1995 was to move away from adversarial bargaining to joint problem-solving and participation by employees on selected issues in order to advance economic development and global competitiveness, social justice, labour peace and the democratisation of the workplace. The drafters of the LRA based the workplace forum system inter alia on the positive and successful statutory employee participation structure in Germany, the works council system. Despite the fact that 22 years after the new LRA came into force there are only 3 workplace forums established in terms of the Act, the legislator still has not made any changes to the provisions yet. This dissertation compares the employee participation structures in South Africa with those in Germany and analyses potential changes - in theory and in praxis - to make the institution of the workplace forum more attractive both to trade unions and employers. The first two chapters give an overview of the statutory system of workplace forums in South Africa and works councils in Germany. The historical background of employee participation, the legal framework as well as the relationship between trade unions and the respective employee representation structure in each country will be discussed. Also, some of the reasons suggested in the literature for the failure of the workplace forum system will be set out. This leads to the third chapter which deals with the prerequisites, under which law can be transplanted from one legal system to another. This is of particular importance as the drafters of the LRA based chapter 5 on the works council system in Germany, adapting it to the South African background though. With reference to the first three chapters, the fourth chapter subsequently proposes several amendments to the LRA which can help in making the workplace forum more attractive for all affected parties. Some of the proposals stem from the positive German experience, others are specifically tailored to the South African context of adversarialism, high unemployment and an economic recession. Proposed amendments are for example: ● Facilitate the establishment of workplace forums by lowering the threshold of 100 employees and by allowing not only representative trade unions but also minority unions and employees to apply for the establishment of a forum. ● Workplace disputes should not be resolved by strikes but by a special dispute resolution mechanism like the German conciliation committee ('Einigungsstelle') to avoid an adversarial and confrontational climate on workplace level. ● Trade unions and workplace forums should be more clearly institutionally and structurally separated. Bargaining councils should be used for centralised bargaining to avoid plant level bargaining. There needs to be a clear demarcation of issues for collective bargaining and issues for workplace forums. In conclusion, this dissertation points out that legal systems emerge under different legal, social and economic circumstances and can therefore not blindly be transplanted from one legal system to another. The preconditions such as the relationship between trade unions, employers and employees, the economic and cultural climate as well as the labour market in South Africa was - at the time of the introduction of the new LRA - and still is completely different from the situation in Germany. Therefore, German provisions regarding works council cannot be transplanted into South African law without measuring them against the South African background. Whereas some German ideas can be adopted, other problematic issues can only be solved with unique South African solutions.